The Response of the Zonally Averaged Circulation to Stratospheric Ozone Reductions. - Schoeberl,M R; Strobel,Darrell F (1978)
The effects of various ozone density reductions on the zonally averaged circulation are evaluated with a numerical quasigeostrophic model. If the ozone perturbations are confined to the polar regions and are minuscule on a global basis as was characteristic of the August 1972 solar proton event, then our calculations indicate a negligible effect on the mean circulation. For global ozone perturbations by predicted halocarbon pollution, we calculate the difference between a 10% reduction in the zonal jet strength and less than a 5% change in global mean stratospheric temperature. Large, uniform ozone reductions ( 50%) produce significant effects on the mean circulation: a substantial collapse of the stratosphere due to cooler temperature and a weak polar night jet. The reflection and transmission of quasi-stationary planetary waves in the middle atmosphere are computed to be insensitive to solar activity as extreme as the August 1972 solar proton event. It thus seems improbable that planetary waves are a viable mechanism for solar-weather interactions that involve perturbations of the zonally averaged circulation by ozone density reductions. (Author)